ANALISIS PERCEPATAN WAKTU PENYELESAIAN PROYEK DENGAN METODE CRASHING DAN FAST TRACKING PADA PELEBARAN JALAN DAN JEMBATAN (Magister Teknik Sipil, Fakultas Teknik, Universitas 17 Agustus 1945 Surabaya, 2019)
To obtain a better profit without ignoring work safety and quality of work, the acceleration ofthe implementation of the work of a construction project can be done using the Crashing andFast Track method. The research objective is to determine the amount of cost and timeincurred by the acceleration of implementation and determine the magnitude of the difference in budget and time spent with the Crashing and Fast Track methods. The Crashing method uses 2 types of variables, namely the addition of 1 hour, 2 hours and 3 hours overtime, andthe addition of heavy equipment and labor, while the Fast Track method uses 3 times theoverlapping application of work items. It turns out that the most optimal result is the additionof 2 hours of overtime work for 163 days so there is a reduction in costs of Rp. 156,358,936,while the Fast Track Method obtained the most efficient results are the results of operationswith a total duration of 130 calendar days, and with a total cost of Rp. 16,812,941,734,38,while the difference between the total plan and the cost after Fast Track is: Rp.340,933,265.63. The Fast Track method is cheaper than the Crashing method which usesovertime hours for 2 hours.Keywords: acceleration of project time and cost, Crashing method, Fast Track method.